2010
DOI: 10.1186/1752-4458-4-23
|View full text |Cite
|
Sign up to set email alerts
|

In the shadow of a new smoke free policy: A discourse analysis of health care providers' engagement in tobacco control in community mental health

Abstract: BackgroundThe prevalence of tobacco use among individuals with mental illness remains a serious public health concern. Tobacco control has received little attention in community mental health despite the fact that many individuals with mental illness are heavy smokers and experience undue tobacco-related health consequences.MethodsThis qualitative study used methods of discourse analysis to examine the perceptions of health care providers, both professionals and paraprofessionals, in relation to their roles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
59
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 34 publications
6
59
1
Order By: Relevance
“…This is in contrast to evidence that smoking cessation, if not actually benefitting mental health, does not impact mental health negatively in people with or without psychiatric disorders 20, even in life‐long, long‐term smokers 21, and that smokers with mental illnesses are just as likely to want to quit as smokers without 22. MHPs have also been reported to hold permissive attitudes towards smoking, such as the belief that smoking with patients can help build a therapeutic relationship 15, 23, 24 and that allowing patients to smoke ensures a smoother running of wards in in‐patient settings 19.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…This is in contrast to evidence that smoking cessation, if not actually benefitting mental health, does not impact mental health negatively in people with or without psychiatric disorders 20, even in life‐long, long‐term smokers 21, and that smokers with mental illnesses are just as likely to want to quit as smokers without 22. MHPs have also been reported to hold permissive attitudes towards smoking, such as the belief that smoking with patients can help build a therapeutic relationship 15, 23, 24 and that allowing patients to smoke ensures a smoother running of wards in in‐patient settings 19.…”
Section: Introductionmentioning
confidence: 63%
“…For instance, previous research has identified that some hold concerns that patients' mental health or abstinence will suffer 14, 15, 16, 17 and that smokers are unable 18 or unmotivated to quit 19. This is in contrast to evidence that smoking cessation, if not actually benefitting mental health, does not impact mental health negatively in people with or without psychiatric disorders 20, even in life‐long, long‐term smokers 21, and that smokers with mental illnesses are just as likely to want to quit as smokers without 22.…”
Section: Introductionmentioning
confidence: 99%
“…While the behavioral health system has come a long way, smoking bans still precipitate concerns about a breakdown of the therapeutic milieu in treatment settings (Johnson et al, 2010). Some behavioral health staff may view tobacco bans with ambivalence, believing that policy enforcement should be someone else's role.…”
Section: Discussionmentioning
confidence: 99%
“…Some behavioral health staff may view tobacco bans with ambivalence, believing that policy enforcement should be someone else's role. Engaging clinical, clerical, and housekeeping staff in the smoke-free policy should include sufficient and ongoing opportunities for input, personal support, and education on both cessation practices and reasoning for the ban (Johnson et al, 2010;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation